EFFECT OF SERVICE QUALITY AND USE OF E – WOM ON CUSTOMER TRUST AT UD TRI PUTRI MEDAN AMPLAS - DEWI (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2023)
This study aims to determine the effect of service quality and use of E-WOM on customer trust at UD. Tri Putri Medan Sandpaper. A sample of 78 customers at UD. Tri Putri Medan Sandpaper. The data analysis technique that the writer uses in this research is descriptive quantitative. The data collection used is by using a questionnaire given to the respondents. The data is processed using SPSS 20.0 for windows. The data analysis technique used is multiple linear regression, with t count for the service quality variable (X1) of 5,483 when compared to the t table value of 1,665. Then the t arithmetic obtained is greater than the t table value or 5.483 > 1.665, then it is also seen that the sig value is smaller than the probability value 0.000 < 0.05 then Ho is rejected and Ha is accepted so that the X1 variable has a contribution to Y. The t value is calculated for the variable Usage E-Wom (X2) is 2,598 when compared to the t table value of 1,665. Then the t count obtained is greater than the t table value or 2,598 > 1,665, then it is also seen that the sig value is smaller than the probability value 0.001 < 0.05 then Ho is rejected and Ha is accepted so that the X2 variable has a contribution to Y. The calculated f value is 180,940 with The sig level is 0.000, therefore the sig value is 0.000 > 0.05 and the calculated F value is 180,940 > F table 2.73. This shows that Ho is rejected so it can be concluded that the independent variables X1, and X2 simultaneously have a positive and significant effect on the dependent variable Y. The value R Square states that service quality and E Wom can explain the effect on customer trust by 0.828 or 82.8%, while the remaining 0.172 or 17.2% is influenced by other variables not included in this study.